2019
DOI: 10.1590/0104-6632.20190364s20180258
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Regeneration of Bone Char Associated With a Continuous System for Defluoridation of Water

Abstract: Sources of fluoride contaminated water are found around the world and their treatment is required before human consumption. This paper contributes to advances in the use of bone-char as an adsorbent for fluoride, associating steps of chemical regeneration and fluoride adsorption in continuous systems, thereby making feasible the multiple use of the adsorbent. Following the development of low cost treatment of water defluoridation in a fixed bed column, using bone-char, regeneration was carried out with NaOH (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…The values of pore volume and diameter for each of the bone chars are within the range reported by other authors for bone chars (Alkurdi et al 2019;Murillo et al 2012;Nigri et al 2019).…”
Section: Textural and Physicochemical Propertiessupporting
confidence: 89%
See 3 more Smart Citations
“…The values of pore volume and diameter for each of the bone chars are within the range reported by other authors for bone chars (Alkurdi et al 2019;Murillo et al 2012;Nigri et al 2019).…”
Section: Textural and Physicochemical Propertiessupporting
confidence: 89%
“…It can be seen that there is an increase in the intensity of the 556, 600, 961 and 1016 cm -1 bands, corresponding to the PO4 3groups, when the bone is pyrolysed (C500) and at the same time these bands maintain their intensity when saturated with fluoride (CF500). In addition, the 3566 cm -1 band corresponding to the OHincreases when the Bone sample is pyrolysed, revealing the formation of hydroxyapatite, and this band is attenuated when saturated with fluoride, which may indicate an interaction between the hydroxyl groups of hydroxyapatite and fluoride (Nigri et al 2019). The mass-loss (TG) and derivative mass-loss (DTG) curves of Bone, C500 and CF500 samples are exhibited in Fig.…”
Section: Sem Ir Tga and Drx Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several studies have reported that hydroxyapatite is an alternative material for fluoride removal. Hydroxyapatite can remove fluoride by exchanging between OH-group on hydroxyapatite and fluoride ion in water [ 14 , 21 , 33 , 38 ].…”
Section: Discussionmentioning
confidence: 99%